A clinical trial for bone void filler made from derived hydroxyapatite from cockle shell mixed with rice starch - Sittiporn Punyanitya (2018)
© 2018 Trans Tech Publications, Switzerland. In this study, we have demonstrated that bone void filler made from hydroxyapatite (HAP) which derived from cockle shell. This sample mixed with rice starch and can be used to augment new bone growth in the empty space defects of damaged hard tissue, such as bone, spine and skull. The chemical compositions of HAP get along with standard specification for composition of ceramic HAP for surgical implants (ASTM International: F1185-88). The starch content was in the safety range of classical cell culture formulation. 60 patients were treated with this bone void filler show successfully healing and recovery, after 6 months period of follow up, confirmed safety and efficacy of the medical device properties. It should be an alternative choice for bone substitute in the future.